Teachers’ attitudes on the contribution of media in teaching Serbian language and literature - Dmitrić, Marijana (Norma, 2025)
Summary: The aim of this paper is to examine the attitudes of teachers and students about the introduction of media culture and the use of modern media in teaching Serbian language and literature in younger grades of elementary school. The research used a descriptive method, the research technique was surveying, and the research instruments were a questionnaire for teachers and a questionnaire for students. The survey questionnaire for teachers aims to determine teachers’ opinions and attitudes about the use of media in teaching Serbian language and literature in younger grades of primary school, as well as the frequency of media use in practice, and contains open, closed and combined type questions. The student questionnaire contains closed, open, and combined questions and aims to examine the views of younger students on the frequency of using media in teaching and the effects they produce. The population consists of first, second, third and fourth grade students of the “Petar Petrović Njegoš” Elementary School in Vrbas and teachers from the elementary schools of Vrbas, Kucura and Savino Selo. The data show that teachers are aware of the didactic potential of media in teaching and that they contribute to better student activity, increased retention of knowledge, and higher quality of teaching. Although teachers believe that media can have a positive impact on education, they are unable to use them sufficiently in teaching practice because the schools in which they work are not sufficiently equipped with innovative communication and information technologies. This situation runs counter to the wishes and opinions of students who stated that they would find it interesting to study with shows and films in class and that their success in school would be better if teachers used modern teaching aids. Keywords: media, contribution of media, information and communication tools, Serbian language and literature, media literacy, traditional teaching, innovations in teaching